Microbiological activity in substrates and growth analysis of tomato seedlings in Guanacaste, Costa Rica - Garbanzo-León, Gabriel; Vargas-Gutiérrez, Marlen (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
The effect of ten mixtures of substrates for seedlings was evaluated. The mixtures were prepared with bocashi, compost and vermicompost, which was used at 50%, then mixed at a ratio of 25% sand, soil, coconut fiber and rice husks. The measured variables included total colony-forming units (CFU/g) of fungi, actinomycetes and bacteria, relative growth rate (RGR) and crop growth rate (CGR) in tomato (Solanum lycopersicum) plants. The experiment was evaluated in Liberia, Guanacaste (Costa Rica). The experiment design was a randomized unrestricted model; and the CFU was measured before the sowing of the nurseries, along with the dry weight for the calculation of the RGR and CGR at 15, 22 and 29 days after sowing. A lower concentration of CFU of fungi (<104 UFC/g) was observed in the mixtures of 50% bocashi + 25% vermicompost + 25% rice husks; 50% vermicompost + 25% sand + 25% soil and 50% compost + 25% bocashi + 25% coconut fiber (50CBF). The highest dry weight treatment was 50% bocashi + 25% compost + 25% coconut fiber (50BCF) and 50CBF (P<0.01). The TCMR in the mixture 50% bocashi + 25% sand + 25% soil was 47% higher when compared to the control (peat moss); 50CBF presented the highest CGR. We concluded that the mixtures 50BCF, 50BAS and 50CBF had the best conditions for tomato plants and peat moss (Sphagnum) was among the five least productive mixtures.